2021
DOI: 10.1371/journal.pone.0257114
|View full text |Cite
|
Sign up to set email alerts
|

Reduced production of the major allergens Bla g 1 and Bla g 2 in Blattella germanica after antibiotic treatment

Abstract: Purpose Allergens present in the feces or frass of cockroaches can cause allergic sensitization in humans. The use of fecal and frass extracts for immunotherapy has been previously investigated but has not yet been fully standardized. Here, we treated cockroaches with ampicillin to produce extracts with reduced amounts of total bacteria. Methods We performed targeted high-throughput sequencing of 16S rDNA to compare the microbiomes of ampicillin-treated and untreated (control) cockroaches. RNA-seq was perfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…Previous research confirmed a reduction in bacterial abundance and diversity in German cockroaches treated with ampicillin [4]. Similarly, we found that cockroaches reared under ampicillin treatment showed reduced amounts of total bacteria in their bodies.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Previous research confirmed a reduction in bacterial abundance and diversity in German cockroaches treated with ampicillin [4]. Similarly, we found that cockroaches reared under ampicillin treatment showed reduced amounts of total bacteria in their bodies.…”
Section: Discussionsupporting
confidence: 89%
“…In a previous study, out of 23 sera from a cockroach-sensitized cohort, 12 (37.5%) showed positive IgE reactivity against recombinant Bla g5 [18]. This study confirmed a reduction in total bacteria caused by antibiotic treatment, as well as changes in gene expression, which led to a reduction of allergen levels [4]. Moreover, IL-6 and IL-8 levels were decreased in airway epithelial cells (BEAS-2B) treated with ampicillin-treated cockroach extract.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…As demonstrated by Myers et al (2018), RNAi can be used to assess the different functions of the different Bla g 2 isomers, multimers, and other proteins. Although there is scientific literature on suppression of the Bla g 2 protein by treating German cockroaches with ampicillin (Lee et al, 2021), there is currently no literature on gene expression silencing of Bla g 2 and any resulting phenotypes. Additionally, co‐immunoprecipitation (Co‐IP) followed by LC‐MS/MS, are other valuable tools to identify and isolate the proteins that interact with Bla g 2.…”
Section: Discussionmentioning
confidence: 99%